The Political Consequences of Supreme Court Consensus: Media Coverage, Public Opinion, and Unanimity as a Public-Facing Strategy - Michael A. Zilis (Washington University Journal of Law & Policy, 2017)
This Article analyses the Supreme Court’s need to tout its unanimous decisions in light of public perception and press coverage. Zilis argues the Court is mindful of the press’ coverage of non-unanimous rulings, which are often framed in unfavorable terms. The Article then argues how public perception of unanimity in the Court can help foster favorable coverage in the press, and increased public approval, by suggesting higher credibility for the Court, limiting the public to competing perspectives, and shaping the public’s understanding of decisions through the media. The Article conclude these strategies can drive public approval and, ultimately, public support for policies adopted by the Court.
Keywords: Supreme Court; Politics; Roberts Court; Media; Public Opinion; Ideology